Hepatoprotective effects of ethanol extract from Gynostemma Pentaphyllum in ethanol induced hepatotoxic rats - Wilaiporn Trakulmututa (Chulalongkorn University, 2007)
Thesis (M.Sc.)--Chulalongkorn University, 2003